Access to maize (zea mays) & its manipulation in huntergatherer contexts in central Argentina (c 3000-2500 bp) - Pastor, Sebastián (2013)
Domesticated maize (Zea mays) was adopted and dispersed across central Argentina by hunter-gatherer communities between c 3000-2500 BP. Primary archaeobotanical evidence for this adoption is derived from two archaeological sites (Quebrada del Real 1, Cruz Chiquita 3) which show the manipulation, processing, and consumption of maize without evidence for other practices of food production. This local case study is integrated into the broader contemporary macro-regional context of southern South America. We analyze and discuss the historical trajectories of hunter-gatherer societies, the dispersion of cultigens including maize, and the mechanisms involved in the expansion of the agricultural frontier.